Metabolic adaptation to a high-fat diet is associated with a change in the gut microbiota. Issue 4 (22nd November 2011) - Serino, Matteo; Luche, Elodie; Gres, Sandra; Baylac, Audrey; Bergé, Mathieu; Cenac, Claire; Waget, Aurelie; Klopp, Pascale; Iacovoni, Jason; Klopp, Christophe; Mariette, Jerome; Bouchez, Olivier; et al.
Abstract : Objective: The gut microbiota, which is considered a causal factor in metabolic diseases as shown best in animals, is under the dual influence of the host genome and nutritional environment. This study investigated whether the gut microbiota per se, aside from changes in genetic background and diet, could sign different metabolic phenotypes in mice. Methods: The unique animal model of metabolic adaptation was used, whereby C57Bl/6 male mice fed a high-fat carbohydrate-free diet (HFD) became either diabetic (HFD diabetic, HFD-D) or resisted diabetes (HFD diabetes-resistant, HFD-DR). Pyrosequencing of the gut microbiota was carried out to profile the gut microbial community of different metabolic phenotypes. Inflammation, gut permeability, features of white adipose tissue, liver and skeletal muscle were studied. Furthermore, to modify the gut microbiota directly, an additional group of mice was given a gluco-oligosaccharide (GOS)-supplemented HFD (HFD+GOS). Results: Despite the mice having the same genetic background and nutritional status, a gut microbial profile specific to each metabolic phenotype was identified. The HFD-D gut microbial profile was associated with increased gut permeability linked to increased endotoxaemia and to a dramatic increase in cell number in the stroma vascular fraction from visceral white adipose tissue. Most of the physiological characteristics of the HFD-fed mice were modulated when gut microbiota was intentionally modified by GOS dietary fibres. Conclusions: The gut microbiota is a signature of the metabolic phenotypes independent of differences in host genetic background and diet.